Cross-sector social partnership success: A process perspective on the role of relational factors. Issue 6 (December 2016) - Barroso-Méndez, María Jesús; Galera-Casquet, Clementina; Seitanidi, Maria May; Valero-Amaro, Víctor
Abstract: The study employs partial least squares structural equation modelling to examine cross-sector social partnership success in the context of Spanish business ( N  = 102). Proposing the development of second-order models, the research identifies the role of relational factors that directly and indirectly affect partnership success. The study demonstrates that to increase partnership success, it is essential for socially responsible businesses to share the same values with their non-profit partners, thus contributing to trust and commitment and effectively enhancing relational effects. Employing relational factors for the conceptualisation of partnership success contributes an empirical quantitative process perspective that associates success with value creation processes.